2014
DOI: 10.1007/s10668-014-9545-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of socio-cultural experiences on residents’ satisfaction in Ikorodu low-cost housing estate, Lagos state

Abstract: This study examined the influences of socio-cultural experiences on residents' housing satisfaction in Ikorodu low-cost housing estate in Lagos State. This study was carried out with the aid of questionnaire administration and reconnaissance survey. The result of the survey shows that the total numbers of the housing units in the area were 119 buildings which comprised 106 bungalows and 13 story buildings. The estate was stratified into two (2) zones which were story buildings and bungalow buildings. Using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
(28 reference statements)
3
29
0
1
Order By: Relevance
“…Dwelling size was also found to be an important predictor of residential satisfaction in the works of Ibem and Aduwo [31], Ibem and Amole [32,33] in the Nigerian context, Buys and Miller [25] in the Australian context, and Wang and Wang [34] in the Chinese context. Larger dwelling size may improve residential satisfaction [35,36]. However, Li et al [37] found, in their study in the Chinese context, that dwelling size does not matter for the migrant workers who were living in the rental housing as temporary dwellers.…”
Section: Dwelling Characteristicsmentioning
confidence: 93%
“…Dwelling size was also found to be an important predictor of residential satisfaction in the works of Ibem and Aduwo [31], Ibem and Amole [32,33] in the Nigerian context, Buys and Miller [25] in the Australian context, and Wang and Wang [34] in the Chinese context. Larger dwelling size may improve residential satisfaction [35,36]. However, Li et al [37] found, in their study in the Chinese context, that dwelling size does not matter for the migrant workers who were living in the rental housing as temporary dwellers.…”
Section: Dwelling Characteristicsmentioning
confidence: 93%
“…Culture is an all-inclusive notion, and its meaning could be derived from the collected studies which cover three major areas that influence residents' satisfaction and socio-cultural experiences of people in housing [67]. Culture in the housing development perspective simply means the process by which individuals adapt to their environment [68].…”
Section: Cultural Dimension Of Residential Satisfactionmentioning
confidence: 99%
“…The concept has been studied in several fields related to housing studies and it studies date back to the 1940 [8]. Household"s satisfaction with residential environment determines their quality of life and an achievement of their needs and aspirations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The households can adjust housing by reviewing their housing aspirations, by making in-situ adjustment through housing modifications and finally adjust by residential mobility [22]. Studies have shown that there is link between residential satisfaction and socioeconomic and demographic characteristics of the households [13], [23], [24], [25], [14] & [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation